ETHNOGRAPHIC STUDY OF ECO-COSMOLOGY OF HO COMMUNITY OF JHARKHAND - Kumari, Neha; Pandey, Rajanikant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Eco-cosmology, as a field of knowledge, reflects upon human perception, relationships, and adaptability to the immediate planetary environment. People in every society have their own conceptual cognitive categories and associated indigenous knowledge about ecology and cosmology. The purpose of this paper is to discuss eco-cosmological knowledge of the Ho people of West Singhbhum districts of Jharkhand, India. The present paper ethnographically elaborates the origin myth relating to land, plants, animals, and human beings and beliefs about celestial bodies like the sun, moon, and stars and geo-climatic events like earthquakes, thunder, storms, rain, seasonal variations, day and night, etc. Further, the younger generation’s exposure to local knowledge in the present context is explored to assess the continuity and change in traditional eco-cosmology. Therefore, the paper fills the existing void in field of eco-cosmological knowledge pertaining to the Ho of Jharkhand.